Epigenetics in psychiatry - Peedicayil, Jacob; Grayson, Dennis R.; Avramopoulos, Dimitri (San Diego, CA : Academic Press, 2014)
Epigenetics in Psychiatry covers all major areas of psychiatry in which extensive epigenetic research has been performed, fully encompassing a diverse and maturing field, including drug addiction, bipolar disorder, epidemiology, cognitive disorders, and the uses of putative epigenetic-based psychotropic drugs. Uniquely, each chapter correlates epigenetics with relevant advances across genomics, transcriptomics, and proteomics. The book acts as a catalyst for further research in this potentially very important and useful area of psychiatry. The elucidation of basic principles o.
Concluding remarksAcknowledgments; References; Glossary; 5 Role of Epigenetics in the Brain; Introduction; Role of epigenetics in evolution; Role of epigenetics in brain development; Brain development; Epigenetics in early brain development; Epigenetics in adult neurogenesis and later brain maturation; Epigenetics and extrinsic factors regulating brain development; Role of epigenetic mechanisms in brain function; Epigenetics and memory; Epigenetics and stress; Epigenetics and cognitive dysfunction; Concluding remarks; Acknowledgments; References; Glossary.
Includes index.
Print version record.
Keywords: Mental illness -- Etiology; Mental illness -- Pathophysiology; Neuropsychiatry; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Mental illness -- Etiology; Mental illness -- Pathophysiology; Neuropsychiatry; Mental Disorders -- etiology; Neuropsychiatry; Electronic books